Controlling tip vortices and cavitation with a grooved-tip design for tidal turbines (Proceedings of the European Wave and Tidal Energy Conference, 2025)
Cavitation can result in blade erosion, vibration, and cavitation noise due to bubble collapse. Tidal turbines' blade tips experience the highest flow speed, and thus, risks of cavitation increase due to low pressure inside tip vortices at high Tip Speed Ratios (TSRs). This can cap their power efficiency and lead to an upper TSR limit. The present work focuses on controlling tip vortices through a novel approach: tip permeability achieved by a grooved tip design. A blade-resolved Reynolds-Averaged Navier-Stokes simulation has been carried out on a model-scale horizontal-axis turbine. In our work, the simulation results have been validated with existing experimental data from the UK Supergen Benchmarking turbine and our wing tip vortex measurements in a water tunnel. We modelled a porous zone placed over the blade tip section, demonstrating that there is an optimal permeability that can substantially reduce the tip vortex intensity and associated pressure drops, and thus mitigate the risk of cavitation. Building on this conclusion, in this study, we have developed a novel design with multiple grooves distributed along the blade tip chord, resulting in an equivalent local 2D permeability. The spanwise scope of the porous or grooved zone is 0.1% of the turbine diameter. It is found that the grooved tip design can significantly increase the minimum pressure coefficient at the tip vortex core by up to 27% at a TSR of 6. We also explored different groove channel designs, either by pitching the grooves or making them convergent. We found that, although the effects remain significant and relatively consistent across all design types, the tip vortices are most effectively suppressed when the groove channel has a convergent shape. This promising outcome suggests a substantial reduction of the tip vortex cavitation risks and can thus enable turbines to operate at higher TSRs. Additionally, as the spanwise extent of the permeable tip is minimal, the impact on the turbine's power and thrust coefficients is slight.